Energy for world agricluture - Stout, B. A. (Rome, 1979)
The second edition of this book was published at the end of 1970. Within a short time thereafter, need was felt to bring out the third edition. While the task of revising the book was in hand, it was felt necessary to bring out immediately as an interim measure a reprint of the book with a supplement and this was done in 1974. The third edition would have made its appearance much earlier had it not been for the dramatic developments in the country since June, 1975, and the state of uncertainty prevailing in the area of constitutional law since then. First, when the book was half-way through in the press, internal emergency was pro claimed on June 25, 1975. Thereafter, a number of constitutional amendments were enacted during the emergency period culminating in the controversial and debatable Forty-Second Amendment in December, 1976. After the general election in March, 1977, the Janata Government assumed office at the Centre. This government is wedded to undoing the Forty-Second Amendment. The Forty-Third Amendment has now been passed but it is only a partial, and not a comprehensive, measure as it supersedes only some of the noxious provisions of the Forty-Second Amendment. It is proposed to enact another constitutional Amendment to further repeal some other provisions of the Forty-Second Amendment. All these events caused delay in the finalisation of this publication as it was thought expedient that all recent developments be incorporated in the book so that an up-to-date picture of the Indian Constitution may be presented to the readers. A discussion of all the amendments made so far is to be found in the last chapter.
Keywords: India Constitutional law